PREPARASI, KARAKTERISASI DAN APLIKASI TiO2(ET)/RESIN SEBAGAI FOTOKATALIS PADA FOTOREDUKSI ION Cu(II) - , MUSLIMIN; , Prof. Dr. Endang Tri Wahyuni, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
To increase photocatalitic activity of TiO2, the preparation and characterization of TiO2 photocatalyst on resin accompanied with photoactivity test for Cu(II) ion photoreduction, have been carried out. The dispersion of TiO2 on resin was carried out by mixing TiO2 that had been suspensed in ethanol (TiO2(et)) with resin, then continued with the ethanol evaporation at temperature 60-70 oC. The characterizations were carried out by using X-Ray diffraction (XRD), FTIR and Diffuse Reflactance UV (DR-UV) methods. Photoreduction process was executed in batch system, by irradiating mixture of Cu(II) solution and TiO2(et)/resin photocatalyst. The influences of photocatalyst mass, Cu(II) ion concentration, andirradiating time towards photoreduction result were also evaluated. The research results showed that TiO2(et)/resin dried at 60-70 oC does not destroy resin and TiO2 structure. Result of activity examination showed that TiO2(et)/resin photocatalyst has highest activity (94.52%) on Cu(II) ion photoreduction followed by TiO2/resin (91.44%) and TiO2 (67.58%). The increase of photocatalyst mass (5-50 mg), could improve the effectivness of the photoreduction, but further increase of mass (50-100 mg) could reduce it. A low Cu(II) concentration (10 mg/L) yielded effective photoreduction (93.44%), but for higher concentration (15-100 mg/L) decreased photoreduction effectivity (89.24- 86.41%). The irradiating time of 1-24 hours increased effectivness of Cu(II) ion photoreduction, but for longer irradiating than 24 hours, photoreduction effectivity was decreased.